Dynamics of Government Support for the Business Feasibility of Islamic-Based MSMEs in East Java - Yusroh Fajariyah; Abdur Rohman (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
This study aims to analyze government support for the viability of Islamic economy-based MSMEs in East Java and identify challenges faced in implementing sharia-based policies. The method used is descriptive qualitative with literature review techniques, where data is collected from various sources such as journals, books, research reports, and related policy documents. The analysis was conducted using content analysis to identify patterns, trends, and the impact of policies on the development of Islamic economy-based MSMEs. The results of the study indicate that government support plays an important role in improving the business viability of Islamic economy-based MSMEs, particularly through sharia-based policies, interest-free financial facilities, and empowerment programs aligned with Islamic economic principles. However, policy implementation still faces various challenges, such as a lack of understanding of Islamic economics among business actors and regulatory challenges that need to be aligned with sharia principles. Additionally, this study highlights how Islamic economy-based MSMEs can leverage government support to enhance their competitiveness and business sustainability. Thus, this research contributes to understanding the interplay between government policies, business viability, and the development of Islamic economics at the regional level.